Enhancement of Science Literacy and Cosmetic Formulation Skills Among High School Students Through Solid Perfume Balm Workshop - Untung Gunawan; Keiko Weimy Ho; Valerina; Allessandra Gabriella Wijaya; Birgitta Evania Hotyus; Yulius Evan Christian (LP2M INSURI Ponorogo, 2026)
High school students' knowledge of cosmetics is generally limited to finished products, without understanding their composition, formulation processes, or safety aspects, which may increase the risk of improper product use. This community service activity aimed to enhance scientific literacy, cosmetic safety awareness, and formulation skills among high school students through an experiential learning-based solid perfume balm workshop, an approach not yet widely implemented in the Indonesian high school context. A pre-post design without a control group was employed with 21 Grade XI Science students (52.38% male; mean age 16.4 years) at SMA Katolik Ricci 1, Jakarta. The evaluation instrument consisted of 10 validated multiple-choice questions. Because the Shapiro-Wilk test confirmed non-normality of difference scores (W = 0.7774; p = 0.0003), the Wilcoxon Signed Ranks Test was used for hypothesis testing. Participant satisfaction was assessed with a seven-item Likert-scale questionnaire. The mean score increased from 77.62 (pretest) to 90.48 (posttest). The proportion of participants with high knowledge rose significantly from 61.90% to 95.24% (Z = −3.823; p < 0.001; effect size r = 0.83). All participants successfully produced their own perfume balm product. The mean satisfaction score was 4.74 out of 5.00. An experiential learning workshop integrating cosmetic safety, formulation skills, and science literacy proved effective for high school students. Recommended follow-up actions include control-group designs, larger samples, and long-term knowledge retention assessments.